High Israeli mortality rates from diabetes and renal failure - Can international comparison of multiple causes of death reflect differences in choice of underlying cause?. Issue 1 (December 2015) - Goldberger, Nehama; Applbaum, Yael; Meron, Jill; Haklai, Ziona
Abstract Background The age-adjusted mortality rate in Israel is low compared to most Western countries although mortality rates from diabetes and renal failure in Israel are amongst the highest, while those from cardiovascular diseases (CVD) are amongst the lowest. This study aims to assess validity of choice of underlying causes (UC) in Israel by analyzing Israeli and international data on the prevalence of these diseases as multiple causes of death (MCOD) compared to UC, and data on comorbidity (MCOD based). Methods Age-adjusted death rates were calculated for UC and MCOD and the corresponding ratio of multiple to underlying cause of death (SRMU) for available years between 1999 and 2012. Comorbidity was explored by calculating cause of death association indicators (CDAI) and frequency of comorbid disease. These results were compared to data from USA, France, Italy, Australia and the Czech Republic for 2009 or other available year. Results Mortality rates for all these diseases except renal failure have decreased in Israel between 1999 and 2012 as UC and MCOD. In 2009, the SRMU for diabetes was 2.7, slightly lower than other Western countries (3.0–3.5) showing more frequent choice as UC. Similar results were found for renal failure. In contrast, the SRMU for ischemic heart disease (IHD) and cerebrovascular disease were 2.0 and 2.6, respectively, higher than other countries (1.4–1.6 and 1.7–1.9, respectively), showing less frequent choice as UC. CDAI data showed a strong association between heart and cerebrovascular disease, and diabetes in all countries. In Israel, 40 % of deaths with UC diabetes had IHD and 24 % had cerebrovascular disease. Renal disease was less strongly associated with IHD. Conclusion This international comparison suggests that diabetes and renal failure may be coded more frequently in Israel as UC, sometimes instead of heart and cerebrovascular disease. Even with some changes in coding, mortality rates would be high compared to other countries, similar to the comparatively high diabetes prevalence in Israel at older ages and high rate of end-stage renal failure. This study highlights the importance of physician training on death certification practice and need for further progress towards automation in recording and coding death causes.